2016
DOI: 10.1007/s12351-016-0276-3
|View full text |Cite
|
Sign up to set email alerts
|

The extent of EFQM effectiveness in routine and non-routine organizations based on multivariate techniques: an empirical study

Abstract: Despite the fact that a variety of analyses are conducted based on the performance of business excellence models according to organization type such as ownership, size and etc., the performance of organizations based on the factor of being routine or non-routine has not been investigated yet. In this paper, implementation of the European Foundation for Quality Management (EFQM) model for these types of organizations (routine and non-routine) has been examined. In order to do that, first we have developed a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…The reliability of a BEF refers to its ability to consistently advance BE in organisations that use it and to accurately measure BE (Sekkizhar and Jagajeevan, 2016;Calvo-Mora et al, 2015). Studies have found that organisations that use BEFs (Bagheri et al, 2019) and the organisations that have won BEAs (Lasrado and Uzbeck, 2017;Bou-Llusar et al, 2005;Curkovic et al, 2000) are higher-performing organisations than others and whilst the EFQM excellence model and the MBEF are found to be accurate measures of BE (Mellat-Parast, 2015;Heras-Saizarbitoria, 2012), Figure 1 The current EFQM Excellence model the other BEFs that are adopted and modified versions of these BEF are found to be equally as accurate in this regard (Raharjo et al, 2015). Flynn and Saladin (2001) attributed the validity and reliability of these two main BEFs to the regular reviews and updates of these BEFs.…”
Section: Business Excellence Framework Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of a BEF refers to its ability to consistently advance BE in organisations that use it and to accurately measure BE (Sekkizhar and Jagajeevan, 2016;Calvo-Mora et al, 2015). Studies have found that organisations that use BEFs (Bagheri et al, 2019) and the organisations that have won BEAs (Lasrado and Uzbeck, 2017;Bou-Llusar et al, 2005;Curkovic et al, 2000) are higher-performing organisations than others and whilst the EFQM excellence model and the MBEF are found to be accurate measures of BE (Mellat-Parast, 2015;Heras-Saizarbitoria, 2012), Figure 1 The current EFQM Excellence model the other BEFs that are adopted and modified versions of these BEF are found to be equally as accurate in this regard (Raharjo et al, 2015). Flynn and Saladin (2001) attributed the validity and reliability of these two main BEFs to the regular reviews and updates of these BEFs.…”
Section: Business Excellence Framework Reliabilitymentioning
confidence: 99%
“…It was found that previous research on designing, developing and modifying BEFs focussed on: identifying the core values and concepts of the BEFs (Jankalova et al , 2018; Asif et al , 2011); the relationships between their criteria (BEFs’ validity) (Mai et al , 2018; Bou-Llusar et al , 2009; Calvo-Mora et al , 2005; Wilson and Collier, 2000) and their reliability in accurately and consistently operationalising and measuring BE (Bagheri et al , 2019; Jayamaha et al , 2009; Jayamaha et al , 2008; Flynn and Saladin, 2006; Flynn and Saladin, 2001). Whilst the prior research studies focus on “what” BEFs are, this research collects data directly from BECs to investigate “how” they design and develop their BEFs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this model incorporates fuzzy Logic. The model's verbal phrase can have multiple meanings thanks to fuzzy Logic [9]. When fuzzy Logic is incorporated into the EFQM model, it becomes more accurate and dependable.…”
Section: Introductionmentioning
confidence: 99%
“…EFQM gives model firms a competitive edge, helping all interest groups [12]. EFQM's self-evaluation model [13]. Expert decisions change the model's subjectivity and applicability.…”
mentioning
confidence: 99%